Three Men and an Abbey: The Cornaro Triple Portrait - Healy, Rachel (My University, 2025)
This paper builds on the author’s recent identification of an early sixteenth-century painting in the National Gallery of Ireland as containing rare portraits of Giorgio Cornaro (brother of Caterina, Queen of Cyprus) and his son Cardinal Francesco. It resolves similar long-standing confusion regarding the identities of sitters in a related work by Titian and his workshop, the Cornaro triple portrait in Washington D.C. In so doing, it will cast new light on Titian’s development as a portraitist and the extent to which important paintings commissioned by the Cornaro survived fires at two family palaces in Venice in the 1530s. The current title of the Cornaro triple portrait is ‘Girolamo and Cardinal Marco Cornaro, investing Marco, abbot of Carrara, with his benefice’ based on unpublished notes by Douglas Lewis in 1972. This paper presents evidence to suggest that the painting should be retitled to ‘Giacomo and Cardinal Marco Cornaro, investing Andrea, abbot of San Zeno, with his benefice’.
PUBLISHED
Keywords: European History